Research progress of hydrogel therapy to improve hypoxic environment of periodontal tissues and promote periodontal regeneration - Jing Zhou; wen lei Wu; Yu Liu (Journal of Oral Biology and Craniofacial Research)
Periodontitis is a hypoxic infectious disease. When periodontal tissues are affected by disease and the microenvironment becomes inflamed, the release of local inflammatory factors and increased tissue metabolism lead to an imbalance between oxygen supply and demand. This inflammatory environment disrupts blood microcirculation, causing the local periodontal tissue to enter a relatively ischemic and hypoxic state. Deep periodontal pockets and periodontal pathogenic bacteria further reduce the oxygen tension in periodontal tissues, exacerbating the progression of periodontitis. Current treatment strategies for improving the inflammatory microenvironment include mechanical therapy and systemic or localized antibiotic administration. However, these existing methods fail to effectively restore the microbiota balance, ensure sustained drug release, or maintain drug presence at the lesion site. Hydrogels, due to their low cytotoxicity, excellent water retention properties, and ability to control drug release, serve as an effective drug delivery pathway that supplies oxygen to inflammatory sites. This article reviews the mechanisms and recent advancements in using hydrogel-based therapies to improve the hypoxic microenvironment of periodontal tissues, thereby promoting periodontal regeneration, and provides clinical insights for future applications in periodontal regeneration.